(untitled) (Proceedings of the International Conference on Agriculture, 2022)
Water stress causes significant problems in plant growth and development in arid and semi-arid regions in the world. Water stress symptoms especially appears during the seedling period of plants in many crops. However, the tolerance of plants to water stress can be increased with some exogenous biostimulant applications. The present study investigated the effect of exogenous biostimulant application on organic acid content of tomato seedlings under water stresses conditions. The study was conducted as pot experiment under controlled greenhouse conditions. Drought stress treatments was applied in two different levels; full irrigation (100%) and 50% of the field capacity in the study. 1% Zn, Bacillus subtilis, Bacillus megaterium, Azosprillum and Bacillus amyloliquefaciens (1x109cfu/ml) mixture were used as a biostimulant treatment. The biostimulant solutions were prepared at a ratio of 1/10 and 1/5 and given to the tomato seedlings three times with one-week intervals as root drench. The effects of water stress and the solutions on organic acid content of tomato seedlings were determined in the study. The results were differed depending on the organic acid type under water stress and non-stress conditions. However, depending on the application doses; the negative effect of lower irrigation level on the organic acid content was alleviated. The results of the biostimulant application doses found statistically significant. In most of the organic acids, the application dose makes massive differences on the content of the organic acids. As a result, it is thought that the effect of lower irrigation level on tomato seedlings in terms of organic acid content can be improved by exogenous biostimulant applications.